Review on Medicinal Importance of Moringa Olifera Leaf for Treating Anemic Conditions: Pharmaceutical Scineces-Pharmacy for Better Health - S, Gejalakshmi; .N, Harikrishnan; .A, Divyasri; .G.E, Thillai Govindarajan (International Journal of Life Science and Pharma Research, 2021)
Moringa olifera is a traditional medicinal plant that belongs to family moringaceae. It is also called as “Miracle tree”. It is rich in alkaloids, flavonoids, essential amino acids and considered as one of the highly nutritious plants. Moringa olifera a multiuse plant is used as a food and medicinal uses. It has various pharmacological activities such as analgesic, antiinflammatory, antipyretic, anticancer, antioxidant, nootropic, hepatoprotective, gastroprotective, antiulcer, anticancer, antioxidant, hepatoprotective, gastroprotective, cardiovascular, antiobesity, antiasthamatic and antidiarrheal properties. This review is a collective summary of phytochemical, pharmacological activity and therapeutic importance of this medicinal herb. Moringa olifera has numerous medicinal uses and it is used to treat many diseases conditions. The review has focused on various properties of Moringa Olifera and therapeutic importance of moringa olifera and its chemical constituents Moringa oleifera is considered to be one of the beneficial plant which has higher medicinal values. Its various nutritional properties made the people across the world to use for its health benefits. The leaf of moringa is considered to have more effective property in curing many diseases though other parts of Moringa oleifera possess less effective properties. The chemical compound of Moringa leaf has high content when compared to other parts and some chemical compounds are present only in leaf of Moringa. Moringa leaf can be used for various health conditions such as Anaemia, Diabetes, Asthma, Inflammation, and Ulcer, Tumor growth, Microbial growth and Plasmodia (Malaria). Anaemia is one of the threatening disorder which is spread all over the world, anaemia occur due to various conditions in which majority is iron deficiency anaemia due to low iron content in plasma. The decrease in haemoglobin will give rise to anaemic condition. From traditional medicine literature study, IDA can be treated by daily consumption of Moringa leaf syrup. The review w